A stochastic inventory model with stock dependent demand items. (2001) - Benkherouf, Lakdere; Boumenir, Amin; Aggoun, Lakhdar
Abstract : In this paper, we propose a new continuous time stochastic inventory model for stock dependent demand items. We then formulate the problem of finding the optimal replenishment schedule that minimizes the total expected discounted costs over an infinite horizon as a Quasi-Variational Inequality (QVI) problem. The QVI is shown to have a unique solution under some conditions.